2019
DOI: 10.1002/pca.2841
|View full text |Cite
|
Sign up to set email alerts
|

Effective MDR reversers through phytochemical study of Euphorbia boetica

Abstract: Introduction Macrocyclic diterpenes from Euphorbia species were found to be promising modulators of multidrug resistance (MDR), a complex phenomenon that hampers the effectiveness of cancer therapy. Objective To find new effective MDR reversers through the phytochemical study of E. boetica, including isolation and molecular derivatisation. Material and methods The phytochemical study of E. boetica was performed through chromatographic techniques. Preliminary analysis of crude chromatographic fractions from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The combination of the essential oil (25 µg/mL) and doxorubicin at different concentrations in HL-60R cells also caused a significant potentiation in the induction of cell death (Table 6 and Figure S2). Our results agree with those reported by Neto et al [56] and Reies et al [57] that show that Euphorbia secondary metabolites were more efficient than verapamil in reverting MDR phenotypes. For this reason, we hypothesize that E. intisy EO can represent an effective and non-toxic P-gp inhibitor to reverse P-gp-mediated multidrug resistance and improve the potency of anticancer drugs.…”
Section: Cytotoxic and Cell Death Effects Of E Intisy Eo In Combination With Doxorubicinsupporting
confidence: 93%
“…The combination of the essential oil (25 µg/mL) and doxorubicin at different concentrations in HL-60R cells also caused a significant potentiation in the induction of cell death (Table 6 and Figure S2). Our results agree with those reported by Neto et al [56] and Reies et al [57] that show that Euphorbia secondary metabolites were more efficient than verapamil in reverting MDR phenotypes. For this reason, we hypothesize that E. intisy EO can represent an effective and non-toxic P-gp inhibitor to reverse P-gp-mediated multidrug resistance and improve the potency of anticancer drugs.…”
Section: Cytotoxic and Cell Death Effects Of E Intisy Eo In Combination With Doxorubicinsupporting
confidence: 93%
“…The activity of reversing MDR was evaluated using a combination of transport and chemosensitivity assays in L5178Y-MDR and Colo320 cell models. The results confirmed the importance of macrocyclic lathyrane diterpenes as effective lead compounds for reversing MDR ( Neto et al, 2019 ).…”
Section: Multidrug Resistancesupporting
confidence: 71%
“…Reis et al (2016) reported that jatrophane diterpenes including esulatin M, epoxywelwitschene, welwitschene, and euphowelwitschine A were more efficative in MDR cells than the positive control verapamil. In comparison to the known MDR modifier verapamil, euphoboetirane C, D, E, F, and G extracted from Euphorbia boetica showed multifold P-gp modulatory activity in L5178Y-MDR cells (Neto et al, 2019). Three types of latilagascenes (G, H and I), macrocyclic diterpene esters, were effective in L5178 cells expressing P-gp as transport inhibitors (Duarte et al, 2008).…”
Section: Phytochemicals Modulating Mdr Targeting Abc-transportersmentioning
confidence: 96%
“…Glaucine exerted synergistic interaction with DOX and even more in a three drug combination with DTN (Eid et al, 2013). Euphoboetirane C, D, F, G, H and I extracted from Euphorbia boetica showed strong synergistic interactions with DOX in L5178Y-MDR cells (Neto et al, 2019). Nobiletin and antofine showed synergistic interactions with PTX (Kim et al, 2012;Ma et al, 2015).…”
Section: Synergistic Combinations Of Chemotherapeutics With Phytochemmentioning
confidence: 99%